Modelling and simulation of SEU in bulk Si and Ge SRAM. (September 2019) - Moindjie, S.; Munteanu, D.; Autran, J.L.
Abstract: In this work, the random-walk drift-diffusion (RWDD) model has been coupled to a circuit simulator to investigate single event upsets (SEU) induced by alpha particles in SRAM cells with silicon or germanium as bulk material. The impact of semiconductor charge generation and transport properties on the SEU mechanisms is quantified and discussed in a first-order approach considering ideal materials and generic devices. Our results suggest that the radiation response of Ge-based SRAM should be similar to the one observed for Si-SRAM, the benefits of higher mobilities at circuit level for germanium offsetting the negative impact of a relatively low energy value for electron-pair creation on transient current pulse magnitudes. Highlights: The radiation responses of germanium and silicon-based SRAM cells have been compared. Numerical simulations investigate the occurrence of single event upsets induced by alpha particles. The impact of semiconductor properties in terms of charge generation and transport has been analyzed. This study gives a first-order indications on the susceptibility of germanium-based SRAM to radiation.